Season‐Dependent Modulation of Pacific Meridional Mode on Tropical Cyclone Genesis Over the Western North Pacific. Issue 1 (1st January 2023) - Fu, Meiling; Wang, Chao; Wu, Liguang; Zhao, Haikun
Abstract: Pacific Meridional Mode (PMM) has been found to be significantly correlated with tropical cyclone (TC) genesis in the western North Pacific (WNP), while the seasonality in their relationship remains unknown. Here we found that their relationship experiences remarkable seasonality, with a significant positive correlation in January–April and August–December but an insignificant relationship in May–July. This seasonality stems from the diverse responses of large‐scale conditions to the different magnitude of the PMM‐related sea surface temperature (SST) warming that is dependent on the strength of trade wind in the three seasons. In January–July, strong trade wind facilitates great PMM SST warming that stimulates large‐scale ascending motion in the eastern WNP but compensated descending motion in the western WNP, favoring TC genesis in January–April because its main genesis region is in the eastern WNP. However, the main genesis region extends to the whole WNP in May–July, the inconsistent large‐scale condition anomalies across the western and eastern WNP thus lead to the insignificant relationship in May–July. In August–December, the PMM‐related SST warming and the associated ascending motion fade away due to the much‐weakened trade wind, and the favorable large‐scale ascending motion over the whole WNP is linked to the PMM‐related SST cooling induced descending motion through a modification of the Walker circulation. The results highlight the season‐dependent mechanism of PMM influencing TC genesis and have some insights for improving seasonal forecasting. Plain Language Summary: As the most active tropical cyclone (TC) basin, the western North Pacific (WNP) breeds about one‐third of the global TC genesis number, bringing about enormous disasters to the Pacific islands and Asian coastal regions. Thus, understanding the climate variabilities in TC genesis over the WNP is of prodigious societal and scientific concerns. The Pacific Meridional Mode (PMM), a seasonally evolving mode of coupled climate variability, is significantly correlated with TC genesis in the WNP. However, seasonality in the correlation between the PMM and WNP TC genesis is still unknown. It is found that their relationship is season‐dependent, with a significant positive correlation in January–April and August–December but insignificant in May–July. This seasonality originates from the diverse responses of large‐scale conditions to the different magnitude of the PMM‐related sea surface temperature (SST) warming in the three seasons, which depends on the strength of trade wind. The results highlight the season‐dependent mechanism of PMM influencing TC genesis and have important implications for understanding the variations of TC genesis in the WNP. Key Points: The Pacific Meridional Mode (PMM) is significantly correlated with the western North Pacific tropical cyclone genesis in January–April and August–December but not in May–July This season‐dependent influence stems from the magnitude of the PMM‐related sea surface temperature warming depending on the trade wind strength